Evaluasi Teknis Geometri Jalan Angkut Produksi Sebagai Upaya Percapaian Target Produksi Batubara 20000 ton/bulan di Tambang Terbuka PT. Allied Indo Coal Jaya (AICJ), Perambahan, Kecamatan Talawi, Kota Sawalunto, Sumatera Barat. - Rizky Nanda Putra; Tamrin Kasim (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. Based on the results of the road geometry evaluation, the following results show that the actual straight road width is between 6.2 - 10.2 m, whereas theoretically the width of the straight road must be made 9 m. The actual grade grades from Stockpile to the West Pit range from 6.98% to 15.83%. The cross slope from Pit to disposal is 4%. Superelevation figures are recommended to overcome road bends with a maximum speed of 40 km / h with a width of 12 meters curved road is 4.98%. The actual productivity before repairing the haul road using the dump truck is Hino Ranger FM 260 JD an average of 18.47 Ton / Hour. This productivity has not yet reached the production target set by PT. Alliet Indo Coal Jaya which is equal to 20000 tons / month. As for productivity after road repairs, 20.90 tons / hour. Keywords: Geometry, Stockpile, Haul Road, Productivity, Target.